Supercapacitor Implementation To Prototype Energy Storage System Optimizer in PV System - Zakaria, Muhamad; Multi, Abdul; Sofwan, Agus (International Journal of Advanced Multidisciplinary, 2024)
This research aims to create a prototype of an energy storage optimizer in a PV system using a supercapacitor in combination with batteries. The purpose of adding supercapacitors in this prototype is to maintain battery usage when there is a change in irradiation with a loading source that refers to the amount of electrical current and voltage as a supply of energy. A sudden increase in load without an energy buffer component can affect battery endurance. This can result in a decrease in electrical energy supply. Based on experimental results, it has been found that the battery and supercapacitor complement each other. The battery works more statically while the supercapacitor works more dynamically. Thus, the power output to the load is more stable, and the battery can be more durable because when there are extreme changes in irradiation and load, they can be overcome by supercapacitors.